Willingness to participate in preventive HIV vaccine trials in a community-based cohort in South Western Uganda - Ruzagira, Eugene; Wandiembe, Symon; Bufumbo, Leonard; Levin, Jonathan; Price, Matthew A.; Grosskurth, Heiner; Kamali, Anatoli (Tropical medicine & international health, 2009)
To assess willingness to participate in HIV vaccine trials and possible barriers to participation. methods Questionnaire survey of participants completing a 2-year community-based HIV Vaccine Preparedness Study, followed by cross sectional analysis of data. results 95% of participants were willing to participate in a trial with similar attributes to the Vaccine Preparedness Study. Certain hypothetical trial attributes significantly reduced willingness to participate: The requirement to delay pregnancy (for females) had the largest effect, reducing willingness to participate from 97% to 23% (P < 0.0001). Larger blood draws had the second largest effect: 95–55% (P < 0.0001). The possibility of receiving either candidate vaccine or placebo had the third largest effect: 95–73% (P < 0.0001). Monthly study visits had the fourth largest effect: 95–92% (P < 0.0001). Trial duration longer than 2 years had the least effect: 95–93% (P = 0.0025). Combined attributes reduced willingness to participate from 95% to 43% (McNemar’s v2 = 521.00; P < 0.0001) overall and 97–11% (McNemar’s v2 = 531.00; P < 0.0001) for female participants. Physical harm concerns (adjusted OR = 34.9; 95% CI, 10.4–118) and a low risk behaviour index (adjusted OR = 0.09; 95% CI, 0.01–0.73) were associated with unwillingness to participate. conclusions We found a high level of willingness to participate in HIV vaccine trials in this population. However, certain HIV vaccine trial requirements were associated with reduced willingness to participate. Community as well as individual concerns will have to be carefully addressed in planned HIV vaccine trials.
Keywords: HIV vaccine trial; Willingness; Community-based; Barriers